Digital trends for an effective corporate communication: an in-company project with the german Winery Römmerts Weinwelt - Yang, Liu (2021)
The migration to digital has been long under way and has even been accelerated by the COVID19 pandemic. Having an online presence as well as implementing a digital strategy regarding corporate communication is crucial for companies to thrive and survive in today’s business world, no matter what size and from which industry they are. However, Römmerts Weinwelt is struggling with the wide array of digital tools and platforms available for present-day corporate communication, unclear which one is key to achieve their marketing goal of an increased brand awareness. To give a suitable recommendation, data from 204 respondents were collected in an online survey to examine which digital platforms consumers use and prefer in terms of brand communication and engagement as well as how they consume and discover wine online. In general, the results revealed that while there is no difference in the use of email, Google and messenger platforms among age. The access to social media networks decreases with increasing age, still yet exhibiting a higher frequency of Facebook access among older age groups. Furthermore, while Instagram is preferred among younger age groups and are more likely the source of discovery of new wine producers as well as the further research destination, it is Google and as a further research step the brand’s website for the older age groups. The solution for Römmert is therefore an omnichannel approach, focusing for starters on key platforms such as Google, their own website and the social media networks Facebook and Instagram.